2010
DOI: 10.1159/000312403
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Mast Cell Degranulation by Disodium Cromoglycate Delayed the Regression of Hypoxic Pulmonary Hypertension in Rats

Abstract: Background: Pulmonary vascular remodeling induced by chronic hypoxia regresses after return to normoxia. This regression is associated with an increased amount of collagenase in pulmonary mast cells and increased collagenolytic and elastolytic activity in the lung tissue. Objective: The role of lung mast cells during recovery from chronic hypoxia was tested by the inhibition of their degranulation by disodium cromoglycate (DSCG). Methods: Male Wistar rats (n = 46) were exposed to isobaric hypoxia (3 weeks, F Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Therefore, it may be deduced that an inhibition of mast cell degranulation impairs the development but does not affect the established pulmonary hypertension in rats. On the contrary, it has been shown that prevention of mast cell degranulation by disodium cromoglycate delays the regression of hypoxic pulmonary hypertension following chronic hypoxia in rats, suggesting that mast cell degranulation plays a role in the regression of pulmonary hypertension during the early phase of recovery from chronic hypoxia (Maxová et al 2010).…”
Section: Pulmonary Hypertensionmentioning
confidence: 97%
“…Therefore, it may be deduced that an inhibition of mast cell degranulation impairs the development but does not affect the established pulmonary hypertension in rats. On the contrary, it has been shown that prevention of mast cell degranulation by disodium cromoglycate delays the regression of hypoxic pulmonary hypertension following chronic hypoxia in rats, suggesting that mast cell degranulation plays a role in the regression of pulmonary hypertension during the early phase of recovery from chronic hypoxia (Maxová et al 2010).…”
Section: Pulmonary Hypertensionmentioning
confidence: 97%
“…Moreover, MCs/c-kit expressing cells have been localized along the periphery/adventitial layer of remodelled pulmonary vessels in experimental PH [19-21]. Recently, MC degranulation has been implicated both in the development of pulmonary vascular remodeling in chronic hypoxic rats and in the regression of the remodeling upon bringing them back to normoxia [22,23]. Activated MCs produce several mediators including the biogenic amine serotonin, the cytokines interleukin (IL)-6 and IL-13, and the serine proteases chymase and tryptase that are capable of activating matrix metalloproteases (MMPs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous measurements of cardiac output in normoxic rats, rats exposed to three weeks of hypoxia and rats after 5 and 14 days of recovery in air, did not show any differences (11). If some volume overload occurs at the beginning of hypoxia it lasts for only first few days of acclimatization (14).…”
Section: Discussionmentioning
confidence: 86%